THE EFFECT OF WORKFORCE RECRUITMENT AND PLACEMENT ON EMPLOYEE JOB SATISFACTION AT PT CIPTA AGRO NUSANTARA 3 - Febyola Fraselya; Andi Indriani Ibrahim; Niluh Putu Evvy Rossanty; Moh. Ali Murad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study This aim For analyze influence recruitment and placement power Work to satisfaction Work employees of PT Cipta Agro Nusantara 3. Research This use approach quantitative with method survey . Population study totaling 49 employees and all population made into sample use technique sample saturated . Data collected through distribution questionnaire and analyzed use multiple linear regression with SPSS version 25 assistance . Research results show that recruitment No influential significant to satisfaction work , while placement power Work influential positive and significant to satisfaction work . In a way simultaneous recruitment and placement​ power Work influential positive and significant to satisfaction work . Variable recruitment and placement power Work capable explain amounting to 26.9% variation satisfaction work , while the rest influenced by other factors outside the research model . The findings study show that accuracy placement power Work be one of factor important in increase satisfaction Work employees of PT Cipta Agro Nusantara 3.